Dung fungi from Brazil: Agrocybe pediades (Fr.) Fayod (Basidiomycota) in Cerrado - Calaça, Francisco J. Simões; Cortez, Vagner Gularte; Xavier-Santos, Solange (Scientia Plena, 2020)
In the survey of copromycodiversity from Brazil, we present the first records of the genus Agrocybe for the Cerrado biome, represented by the species A. pediades, found on cattle dung in the state of Goiás, central Brazil. We also present detailed morphological descriptions, illustrations, and comments about its distribution and the fimicolous habitat, as well as the cultural characteristics of the specimens